Answer :

Given: - - - - - - - - (1)

Let


y2 - 5y + 6 = 0 substituting value for y in (1)


Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = 1 b = - 5 c = 6


= 1.6 = 6


And either of their sum or difference = b


= - 5


Thus the two terms are - 3 and - 2


Difference = - 3 - 2 = - 5


Product = - 3. - 2 = 6


y2 - 5y + 6 = 0


y2 - 3y - 2y + 6 = 0


y(y - 3) - 2 (y - 3) = 0


(y - 3)(y - 2) = 0


(y - 3) = 0 or (y - 2) = 0


y = 3 or y = 2


Case I: if y = 3



x = 3x + 3


2x + 3 = 0


x = - 3/2


Case II: if y = 2



x = 2x + 2


x = - 2



Hence the roots of equation are


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

If the roots of tMathematics - Board Papers

Find the roots ofRD Sharma - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics